Proliferation of the human urothelium is induced by atypical β1‐adrenoceptors. (31st May 2016) - Winder, M.; Wasén, C.; Aronsson, P.; Giglio, D.
Summary: We wanted to assess whether β‐adrenoceptors mediate proliferation in the normal and malignant urothelial cell lines UROtsa and T24, respectively. Urothelial cells were cultured for 24 h in the presence of the β‐adrenoceptor agonists isoprenaline (β1/2/3 ), dobutamine (β1 ), salbutamol (β2 ), BRL 37344 (β3 ), CGP 12177 (a partial β‐agonist) or β‐adrenoceptor antagonists (metoprolol; β1, propranolol; β1/2 ). Phosphorylation of kinases was screened with a Human Phospho‐Kinase Array Kit (R&D systems). Intracellular pathways activated by proliferation of urothelial cells were characterized by incubating cells with the MEK1/2 inhibitor PD 98, 059, the p38 kinase inhibitor losmapimod or with the Akt 1/2 kinase inhibitor. Proliferation was assessed with the MTT proliferation assay (ATCC). Western blot and immunocytochemistry were used for detection of the β1 ‐adrenoceptor. Isoprenaline and dobutamine induced proliferation, while salbutamol and BRL 37344 did not. Dobutamine‐induced proliferation was not affected by metoprolol or propranolol but was instead antagonized by CGP 12177 in T24 but not in UROtsa. In response to stimulation with dobutamine, Akt1/2/3 was phosphorylated in UROtsa, while ERK1/2 and p38 were phosphorylated in T24. MEK1/2 inhibition blocked basal and dobutamine‐induced proliferation in T24 but only basal proliferation in UROtsa. Losmapimod slightly inhibited basal proliferation in T24 but not dobutamine‐induced proliferation. Akt 1/2 inhibitor blocked basal and dobutamine‐induced proliferation in UROtsa. Immunocytochemistry and Western blot revealed expression of β1 ‐adrenoceptors in both urothelial cell lines. The present data show that the urothelium expresses atypical β1‐adrenoceptors that activate intracellular kinases inducing urothelial proliferation.